The Regional Western Sweden SOM Survey 2019 - SOM Institute, University of Gothenburg (University of Gothenburg, 2021)
The Regional Western Sweden SOM Survey has been conducted yearly since 1992, but was initially limited to residents of Gothenburg and its surrounding municipalities. In 1998, the survey was extended to include the entire Västra Götaland County plus the municipality of Kungsbacka.

The purpose of the regional surveys is to enable SOM researchers to study attitudes and behaviour linked to local and regional issues. They emphasise public services and media, although many of the questions are identical with those used in National SOM in order to make the answers comparable both between the regions and with Sweden at large.

Den västsvenska SOM-undersökningen har genomförts varje höst sedan 1992. Fram till 1997 omfattade studien Göteborg med kranskommuner. Undersökningen utökades sedan till att omfatta hela Västra Götalands län samt Kungsbacka kommun. Studien genomförs i samverkan med Västra Götalandsregionen och är en del av regionens långsiktiga utvärderingsarbete.

Flertalet frågor har ställts i många år och svaren bidrar till att bibehålla tidsserier som sträcker sig från undersökningens början 1992. Frågorna har tonvikt på attityder och beteenden inom områdena offentlig service och medier. Många av frågorna är identiska med frågor i den nationella SOM-undersökningen vilket ger möjlighet att jämföra data både på regional och på nationell nivå.
Den västsvenska SOM-undersökningen 2019
Väst-SOM 2019
Keywords: housing; boende; occupations; yrken; public sector; offentlig sektor; environment; miljö; trust; förtroende; european union; europeiska unionen; political interest; politiskt intresse; local government services; kommunal service; public transport; kollektivtrafik; medical care; sjukvård; public services; offentlig service; news; nyheter; income; inkomst; political participation; politiskt deltagande; religious practice; religionsutövning; democracy; demokrati; internal politics; inrikespolitik; political parties; politiska partier; internet use; internetanvändning; politicians; politiker; social participation; socialt deltagande; working conditions; arbetsförhållanden; households; hushåll; clubs; föreningar; leisure time activities; fritidsaktiviteter; educational levels; utbildningsnivå; political attitudes; politiska åsikter; CORS; CORS; POLITICS; POLITIK; SOCIETY AND CULTURE; SAMHÄLLE OCH KULTUR; Elections; Val; Political behaviour and attitudes; Politiska beteenden och attityder; Political ideology; Politisk ideologi; Cultural activities and participation; Kulturaktiviteter och deltagande; MEDIA, COMMUNICATION AND LANGUAGE; MEDIA, KOMMUNIKATION OCH SPRÅK; LABOUR AND EMPLOYMENT; ARBETE OCH SYSSELSÄTTNING; Leisure, tourism and sport; Fritid, turism och sport; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Political Science (Excluding Peace and Conflict Studies); Statsvetenskap (exklusive freds- och konfliktforskning); Media and Communications; Medie-, kommunikations-, och informationsvetenskaper; Media and Communication Studies; Medie- och kommunikationsvetenskap; Other Social Sciences; Annan samhällsvetenskap; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap